Gap Analysis of Ship Design Approval Case Study: Key Plan Drawing Assessment for Dual Fuel Harbour Tugboat - Iskendar, Iskendar; Kadir, Abdul; Waluyo, Waluyo; Kartikasari, Dewi; Sadiah, Siti; Priatno, Dany Hendrik; Nugroho, Andi Cahyo Prasetyo Tri; Prasetyo, Fredhi Agung (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2023)
Starting to build the ship, the ship’s designer or builder must prepare key plan drawings with an approval statement that comes from the Classification Society (CS) based on the conformity of key plan drawings to comply with the rules or sometimes do not comply with those rules in several cases, so this situation could be minimized by using a gap analysis technique prior to the approval of the ship design process. Gap analysis is the tool to evaluate whether the design has been conforming to comply with the rules of the classification society or not. This paper chooses some parts of the ship design of a Dual Fuel Harbour Tugboat (DF Tug) to show the level of conformity to the rules. The assessment process involves Biro Klasifikasi Indonesia (BKI) since the DF Tug will be classified by BKI as a competent national classification society. The findings gap is used to improve the design of DF Tug. Finally, the framework of corrections and improvements to the DF Tug design is proposed as part of the refinement of key plan drawings, and the final ship design complies with rules and gets full approval from the classification society